2015
DOI: 10.1021/acs.cgd.5b00504
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear Ni(II)/Co(II)/Mn(II) Complexes Based on Terphenyl–Tetracarboxylic Acid Ligand: Crystal Structures and Research of Magnetic Properties

Abstract: By the solvothermal reactions of a [1,1':3',1''-terphenyl]-3,3'',5,5''-tetracar -boxylic acid (H 4 tpta) with transition metal ions, three novel polymeric complexes, namely,(3) have been isolated. The heterometallic clusters of these polymeric complexes are dimeric and tetrameric, respectively. 1 is comprised of dimeric paddle wheel Ni(II) units to generate a 2D structure.In complexes 2 and 3, metal ions form tetrameric units that extend via all dimensions to give 3D structures with the Schläfli symbol of (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…It can be also self-assembled into a multinuclear secondary structural unit with metal ions to further construct coordination polymer networks of various structures. The carboxyl-and carboxylate rich coordination mode and diverse coordination chemistry are favored by coordination chemists and crystal engineering scholars [4,5]. And the carboxyl oxygen atoms can form hydrogen bonds with a solvent molecule such as water, thereby assembling a supramolecular structure to form a supramolecular compound having a special property [6].…”
Section: Commentmentioning
confidence: 99%
“…It can be also self-assembled into a multinuclear secondary structural unit with metal ions to further construct coordination polymer networks of various structures. The carboxyl-and carboxylate rich coordination mode and diverse coordination chemistry are favored by coordination chemists and crystal engineering scholars [4,5]. And the carboxyl oxygen atoms can form hydrogen bonds with a solvent molecule such as water, thereby assembling a supramolecular structure to form a supramolecular compound having a special property [6].…”
Section: Commentmentioning
confidence: 99%
“…Previous studies on the carboxylate bridged dinuclear metal complexes show that the syn – syn bridging pattern triggers antiferromagnetic exchange interactions between the metal ions, whereas anti – anti and syn – anti bridging modes often lead to weak ferromagnetic or antiferromagnetic couplings. Moreover, it is also well-known that the metal···metal distances as well the coordination geometry around the metal centers affect the extent of magnetic coupling between the adjacent metal atoms. In this present case, from the structural analysis of 1 and 1a (Figure ), it is observed that two syn – syn carboxylate bridges are present between two neighboring magnetically interacting Co II centers for both 1 and 1a .…”
Section: Resultsmentioning
confidence: 99%
“…The χ M T value at 300 K (2.4 cm 3 K mol −1 ) exceeds the desired value (2.0 cm 3 K mol −1 ) slightly for two magnetically isolated Ni(II) ions (Figure 9), reflecting the existence of orbital contribution arising from the high-spin octahedral Ni(II) ions. 53,54 Upon cooling, χ M T declines slowly to reach a rock bottom of 2.2 cm 3 K mol −1 at 35 K, suggesting an antiferromagnetic interaction in the range of 35−300 K. The further temperature decrease results in χ M T rising to the maximum value of 2.43 cm 3 K mol −1 at 6.0 K, indicating a ferromagnetic character. Finally, below 6.0 K, the χ M T decreased again, caused by the zero-field splitting of Ni(II) and/or some kinds of intramolecular antiferromagnetic interactions.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%